The Influence of Competency, Independency, and Professionalism on Audit Quality - Dewi Kartika; Bambang Agus Pramuka (Journal of Accounting and Strategic Finance, 2019)
The purpose of this research is to examine the influence of competency, independency, and professionalism on audit quality. Competency, independency, and professionalism are three characteristics of a competent auditor. The population of this research is the auditor of accounting firms in Central Java. The samples of this research are employees of auditors working at accounting firm (KAP) Budiman, Wawan, Pamudji Tegal, KAP Wartono & Fellow Surakarta, KAP Sophian Wongsaro Semarang, KAP Heliantono & Semarang Branch. Forty-five questionnaires are employed in this study. Before the hypotheses testing, validity and reliability tests are run to determine the validity and reliability of the data. Hypothesis testing techniques use regression analysis. These research results show that competency, independency, professionalism influence the quality of the audit. However, these results have to be cautiously interpreted since only a few auditors’ questionnaires were worth analyzing. Future studies may increase the number of KAPs from other districts in Indonesia or using not only auditors from accounting firms but also government auditors or internal auditors.